Bringing the 'other half' back: a place-specific intergenerational exploration of Indigenous physical cultural masculinities in Fisher River Cree Nation. Issue 5 (20th October 2019) - Norman, M. E.; Hart, M. A.; Petherick, L.; McRae, H.; Mason, G.; Cote, A.; Cote, S.; Sinclair, C.
ABSTRACT: In this paper, we introduce readers to the Indigenous Wellbeing of Boys and Men project, a 4-year research collaboration between scholars from the Universities of Manitoba and British Columbia and Fisher River Cree Nation ( Ochékwi Sipi ). We overview the research design of the project, paying particular attention to the foundational strategies that informed the research process. These strategies included, embedding the project within an Indigenous paradigm, rooting it within the place-specific context of Fisher River Cree Nation, and creating a community-wide and intergenerational dialogue about Indigenous physical cultures and masculinities. We then examine the first phase of the project, which involved sharing circles, to illustrate how these strategies informed the research process. We argue that this design enabled critical insights on the role that physical culture can potentially play in maintaining and revitalising place-specific Indigenous masculinities. This paper brings the burgeoning scholarship in Indigenous methodologies and Indigenous masculinities into conversation with the work in physical cultural studies and, in so doing, makes important contributions to each disciplinary area.